Supporting Healthy Dementia Culture: An Exploratory Study of the Church - Plunkett, Robyn (Journal of religion and health, 2016)
This research used the church as an exemplar to identify how community institutions provide opportunities for individuals living with dementia to continue living in meaningful ways. Study results from this exploratory study indicated churches are moving towards dementia-friendly spaces, but additional assistance is required. Namely, support with the costs of physical infrastructure improvements, dementia education, adequate transportation, and social supports were identified. Due to the significant presence that the church has in lives touched by dementia, policy that acknowledges its contributions to health would help to legitimize the church as a health resource and promote inclusive community culture for individuals in the context of dementia.